Sastra, Pengajaran, dan Pengembangannya - Dwi Sutana (Kantor Bahasa Provinsi Maluku Utara, 2013)
Literature teaching aims to act as a tool to carry forward the values of ethics and morals in life. It is also oneof the means for the development of literature which aims to expand literature field as well as to increase literature appreciation, improve the quality of literature, and to excite literature enthusiasts. These can only beachieved with the implementation of literature teaching. Engaging students with literature will increase their appreciation and interests. Through this way, the teacher can enhance the teaching of literature to be better.The growing literature will open up our mind to new experiences or to invite us to organize these experiences with a new way. Moreover, this can be a tool to generate the people’s opinions in the society